NEEDS ANALYSIS FOR ENGLISH GRAMMAR LEARNING MODEL FROM STUDENTS’ PERSPECTIVES - Wisma Yunita; Emzir Emzir; Ilza Mayuni (University of Kuningan, 2018)
Need analysis is required to take place before developing a model for learning so that results meet the needs of the students who will use the model. This descriptive study aims at finding out the needs in learning English grammar from students’ perspectives at the EESP of the University of Bengkulu. The data was taken through a questionnaire with 65 questions given to 44 students who took Structure I Course in the 2016-2017 academic year and analyzed quantitatively. The results of this study reveal that the students need a clear goals of learning English grammar, learning approaches that uses the story-based, the deductive, and the inductive approach, a friendly and meaningful learning atmosphere, a learning model that incorporates the uses of stories and current technology for the teaching and learning process and has a complete support system especially the learning materials, and has an attitude, a final assignment and an individual learning process result assessments.Keywords: Needs analysis, model, grammar learning